Piezoelectric laminate and piezoelectric element
Patent Information
- Application Number
- JP2023149248
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
AI Technical Summary
【0019】 本開示の技術によれば、従来よりもさらに高い耐電圧及び信頼性を有する圧電積層体及び圧電素子を提供することができる。
Smart Images

Figure 2025042312000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]
[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being deployed in a variety of devices, including memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.
[0003] It is described in Patent Documents 1 and 2 that a piezoelectric film with high orientation and good piezoelectric performance can be realized by adding Nb (niobium) to the B site in a PZT-based perovskite oxide. Patent Document 3 discloses that the piezoelectric performance of a piezoelectric film produced by a sol-gel method can be improved by adding Mn (manganese) in addition to Nb. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-71295 A [Patent Document 2] JP 2014-60330 A [Patent Document 3] International Publication No. 2015 / 146607 Summary of the Invention [Problem to be solved by the invention]
[0005] From the standpoint of device operation and reliability, piezoelectric films with even higher withstand voltages and higher reliability are desired, and research and development is underway to develop piezoelectric films with improved withstand voltages and reliability by controlling the composition as well as the surface roughness.
[0006] The technique disclosed herein has been made in consideration of the above circumstances, and has an object to provide a piezoelectric laminate and a piezoelectric element having higher withstand voltage and higher reliability than ever before. [Means for solving the problem]
[0007] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including a lower electrode layer and a piezoelectric film mainly composed of a perovskite oxide, in this order, on a substrate, When an upper electrode layer is formed on a piezoelectric film and the voltage applied between the upper electrode layer and the lower electrode layer is swept, the lower electrode layer is grounded and the upper electrode layer is used as a driving electrode, and the voltage applied to the piezoelectric film is gradually increased from 0 V to the positive side and then gradually decreased from the positive side to 0 V to the negative side. In the current-voltage curve showing the change in current relative to the change in voltage, the number of peaks when the voltage is increasing is different from the number of peaks when the voltage is decreasing.
[0008] In a current-voltage curve, when the half-width of the peak when the voltage rises is Wu and the half-width of the peak when the voltage falls is Wd, it is preferable that Wu≧1.5×Wd.
[0009] When the number of peaks when the voltage increases is defined as NA and the number of peaks when the voltage decreases is defined as NB, it is preferable that NA>NB.
[0010] It is preferable that the number of peaks NA during the rise of the voltage is one greater than the number of peaks NB during the fall of the voltage.
[0011] It is preferable that the number of peaks NA during the voltage rise is 3, and the number of peaks NB during the voltage fall is 2.
[0012] Perovskite oxides are Pba {(Zr x Ti 1-x ) 1-y M y}O3 M is a metal element selected from the group consisting of V, Nb, Ta, Sb, Mo and W; 0 <x<1、0<y<1、0.9≦a≦1.2 It is preferable that the following is satisfied.
[0013] It is preferable that M is Nb and satisfies 0.08≦y≦0.15.
[0014] In the crystal grain size distribution obtained by electron backscatter diffraction, the piezoelectric film preferably has an average grain size weighted by the area ratio of the crystal grain size of more than 0.25 μm, more preferably 0.3 μm or more, and more preferably 0.4 μm or less.
[0015] It is preferable to provide a seed layer between the lower electrode layer and the piezoelectric film, the seed layer being lattice-matched with the perovskite oxide.
[0016] The seed layer preferably has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal.
[0017] The seed layer is preferably composed mainly of SrRuO3 or BaRuO3.
[0018] The piezoelectric element of the present disclosure includes the piezoelectric laminate of the present disclosure and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. Effect of the Invention
[0019] According to the technique of the present disclosure, it is possible to provide a piezoelectric laminate and a piezoelectric element having higher withstand voltage and higher reliability than ever before. [Brief description of the drawings]
[0020] [Figure 1] 1 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a first embodiment. [Diagram 2] 4 is a schematic diagram of an IV curve showing the current-voltage (IV) characteristics of the piezoelectric element of the embodiment. FIG. [Diagram 3] 5 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a second embodiment. FIG. [Figure 4] 4 shows the IV curve of Example 3. [Diagram 5] 4 shows an IV curve of Comparative Example 1. [Figure 6] This is an example of an image pattern of crystal grains on the surface of a piezoelectric film obtained by the EBSD method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. In the following drawings, the layer thicknesses and their ratios of each layer are appropriately changed for ease of visibility, and do not necessarily reflect the actual layer thicknesses and ratios. In this specification, a numerical range expressed using "~" means a range including the numerical values described before and after "~" as the lower and upper limits. In the numerical ranges described in stages in this disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0022] Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 according to one embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, a lower electrode layer 12, and a piezoelectric film 15 mainly composed of a perovskite oxide, which are laminated in this order on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12, and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.
[0023] The substrate 10 is not particularly limited, and examples thereof include substrates of silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, silicon carbide, etc. The substrate 10 may be a laminate substrate such as a silicon substrate with a thermally oxidized film in which a SiO2 oxide film is formed on the surface of a silicon substrate. The substrate 10 may also be a resin substrate such as PET (polyethylene terephthalate), PEN (polyethylene naphthalate), polyimide, etc.
[0024] The lower electrode layer 12 is an electrode that is paired with the upper electrode layer 18 and applies a voltage to the piezoelectric film 15. The main component of the lower electrode layer 12 is not particularly limited, and examples thereof include metals or metal oxides such as Au (gold), Pt (platinum), Ir (iridium), Ru (ruthenium), Ti (titanium), Mo (molybdenum), Ta (tantalum), and Al (aluminum), as well as combinations thereof. ITO (indium tin oxide) may also be used. The lower electrode layer 12 may be a single layer or a multi-layer structure. When the lower electrode layer 12 has a multi-layer structure, it is also preferable to provide an adhesive layer such as Ti, TiW, or ZrO2 on the substrate 10 side in addition to the conductive layer made of the above material.
[0025] The thickness of the lower electrode layer 12 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm, overall.
[0026] The upper electrode layer 18 is an electrode that is paired with the lower electrode layer 12 and applies a voltage to the piezoelectric film 15. The main component of the upper electrode layer 18 is not particularly limited, and examples thereof include metals such as Au, Pt, Ir, Ru, Ti, Mo, Ta, and Al, or metal oxides thereof, and combinations thereof. ITO (Indium Tin Oxide), LaNiO3, SrRuO3, and the like may also be used. The upper electrode layer 18 may be a single layer or a laminated structure consisting of multiple layers. In order to further suppress oxygen diffusion from the piezoelectric film 15, it is preferable that at least the region of the upper electrode layer 18 that is in contact with the piezoelectric film 15 is an oxide electrode.
[0027] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.
[0028] FIG. 2 is a schematic diagram of a current-voltage (IV) curve obtained by applying a sweep voltage to the piezoelectric film 15 with the lower electrode layer 12 grounded and the upper electrode layer 18 used as a driving electrode. As shown in FIG. 2, the number of current peaks (hereinafter referred to as the number of peaks) differs between when the voltage rises and when the voltage falls in the IV curve of the piezoelectric film 15. The sweep of the applied voltage is performed by increasing the potential applied to the upper electrode layer 18 from 0V to the positive side, and then decreasing it from the positive side to 0V and then to the negative side. In the IV curve, the case where a positive potential is applied to the upper electrode layer 18 is shown as a positive voltage, and the case where a negative potential is applied to the upper electrode layer 18 is shown as a negative voltage. Note that the IV curve is obtained by, for example, changing the voltage applied to the upper electrode layer 18 from 0V to +40V to -40V to 0V with a 10Hz triangular wave and measuring the change in the current value at that time. If one cycle is a triangular wave that changes from 0V to +40V to -40V to 0V, the data may be unstable in the first cycle, but from the second cycle onwards the curve will be stable and will show roughly the same behavior. When counting the number of peaks, a stable IV curve is used. For example, the data from the third cycle can be used.
[0029] In the IV curve of the piezoelectric film 15, when the peak half width when the voltage increases is Wu and the peak half width when the voltage decreases is Wd, it is preferable that Wu≧1.5×Wd.
[0030] In the IV curve, when the number of peaks when the voltage rises is NA and the number of peaks when the voltage falls is NB, it is preferable that NA>NB. In the example shown in Fig. 2, three peaks Pu1, Pu2, and Pu3 occur when the voltage rises, and two peaks Pd1 and Pd2 occur when the voltage falls. That is, the number of peaks NA when the voltage rises is 3, and the number of peaks NB when the voltage falls is 2.
[0031] In addition, the peak half-width Wu when the voltage increases is the half-width when the three peaks Pu1, Pu2, and Pu3 are regarded as one peak Pu as a whole as shown in Figure 2, and the peak half-width Wd is the half-width when the two peaks Pd1 and Pd2 are regarded as one peak Pd as a whole as shown in Figure 2. In this way, the peak half-width Wu when the voltage increases in the IV curve or the peak half-width Wd when the voltage decreases is defined as the full width at half maximum of a single wide peak that includes the multiple peaks when each includes multiple peaks.
[0032] The number of peaks contained in one wide peak is calculated as follows. A smoothing process is performed to remove noise from the acquired IV curve, and the number of points where the derivative f1'(x) of the curve when the voltage increases, for example, when expressed by the function f1(x) in the smoothed IV curve, is 0 is the number of peaks when the voltage increases. Similarly, the number of points where the derivative f2'(x) of the curve when the voltage decreases, is 0 is the number of peaks when the voltage decreases. Alternatively, the smoothed IV curve may be subjected to peak fitting and peak separation assuming a normal distribution or log-normal distribution. The number of peaks can be determined using commercially available data analysis software (such as OriginPro).
[0033] According to JP2010-16011A, an inflection point in the polarization-electric field (PE) hysteresis curve indicates the occurrence of a 180° polarization reversal or phase transition. Since the inflection point in the PE hysteresis curve corresponds to a current peak in the IV curve, the current peak is considered to indicate the occurrence of a 180° polarization reversal or phase transition. Usually, the number of peaks is the same during voltage rise and fall.
[0034] A piezoelectric film having different numbers of peaks when the voltage rises and falls, such as the piezoelectric film 15 in this embodiment, is obtained by performing reverse sputtering on the film formation surface before film formation, and then forming the film. The piezoelectric film 15 obtained in this manner has strong adhesion. Strong adhesion of the piezoelectric film 15 means that the stress is large. In the piezoelectric film 15 having a large stress, a transition phase is formed due to the relaxation of the substrate stress during the phase transition that occurs when the voltage rises, and it is presumed that the occurrence of this transition phase occurs as one peak in the IV curve. On the other hand, when the voltage falls, the stress is released along with the phase transition, so it is considered that no peak occurs. In this way, when the number of peaks when the voltage rises is NA=NB+1, which is one greater than the number of peaks when the voltage falls, it is presumed that the one peak that is the difference is related to the substrate stress.
[0035] For example, the three peaks occurring during voltage increase as shown in Figure 2 are assumed to be associated with a phase transition from the tetragonal a-axis orientation to the c-axis orientation, a 180° polarization reversal, and the occurrence of the above-mentioned transition phase due to substrate stress, while the two peaks occurring during voltage decrease are assumed to be associated with a phase transition from the tetragonal c-axis orientation to the a-axis orientation, and a 180° polarization reversal.
[0036] Furthermore, in cases where a phase transition from tetragonal to rhombohedral occurs with a change in voltage, the number of peaks will be greater than that shown in Figure 2. In addition, one peak generally occurs for one phase transition, but there are also cases where two or more peaks overlap and appear to be essentially one peak. However, as mentioned above, the number of points where the derivative of the curve is 0 is regarded as the number of peaks.
[0037] As described above, the piezoelectric film 15 of the present disclosure mainly comprises a perovskite-type oxide. Here, "mainly comprising a perovskite-type oxide" means that the perovskite-type oxide occupies 80 mol% or more of the piezoelectric film. The piezoelectric film 15 preferably consists of 100 mol% perovskite-type oxide (however, it contains inevitable impurities).
[0038] The perovskite-type oxide is preferably an oxide of lead zirconate titanate (PZT) containing Pb (lead), Zr (zirconium), Ti (titanium) and O (oxygen).
[0039] In particular, it is preferably a compound represented by the following general formula (1) containing an additive M at the B site of PZT. Pb a {(Zr x Ti 1-x ) 1-y M y}O3(1) Here, M is preferably one or more elements selected from V (vanadium), Nb (niobium), Ta (tantalum), Sb (antimony), Mo (molybdenum) and W (tungsten). Here, it is preferably 0 < x < 1, 0 < y < 1, 0.9 ≦ a ≦ 1.2, and more preferably 0.08 ≦ y ≦ 0.15. In the general formula (1), Pb:{(Zr x Ti 1-x ) 1-y M y}:O is based on 1:1:3, but may deviate within the range where a perovskite structure can be obtained.
[0040] M may be a single element such as only V or only Nb, or a combination of two or more elements such as a mixture of V and Nb, or a mixture of V, Nb and Ta. When M is these elements, a very high piezoelectric constant can be realized in combination with the Pb of the A-site element.
[0041] If the piezoelectric film 15 is formed as a sputtered film by a vapor phase growth method such as sputtering, a piezoelectric film having an extremely high piezoelectric constant can be obtained.
[0042] It is said that PZT-based perovskite oxides exhibit high piezoelectric properties at or near the morphotropic phase boundary (MPB). The MPB composition is when Zr:Ti (molar ratio) is close to 52:48, and in the above general formula, the MPB composition or its vicinity is preferable. "At or near the MPB" refers to a region where a phase transition occurs when an electric field is applied to the piezoelectric film. Specifically, the Zr:Ti (molar ratio) is preferably within the range of 45:55 to 55:45, that is, within the range of x = 0.45 to 0.55.
[0043] The thickness of the piezoelectric film 15 is preferably 0.2 μm or more and 5 μm or less, and more preferably 1 μm or more.
[0044] In the crystal grain size distribution obtained by the electron backscattered diffraction (EBSD) method, the piezoelectric film 15 preferably has an average grain size of 0.3 μm or more, weighted by the area ratio of the crystal grain size.
[0045] In this manner, the piezoelectric laminate 5 of this embodiment includes a lower electrode layer 12 and a piezoelectric film 15 mainly composed of a perovskite oxide on a substrate 10 in this order, an upper electrode layer 18 is formed on the piezoelectric film 15, and a voltage applied between the upper electrode layer 18 and the lower electrode layer 12 is swept, the lower electrode layer 12 is grounded, the upper electrode layer 18 is used as a driving electrode, and the voltage applied to the piezoelectric film 15 is gradually increased from 0V to the positive side, and then gradually decreased from the positive side to 0V to the negative side. In the IV curve showing the change in current with respect to the change in voltage, the number of peaks when the voltage rises is different from the number of peaks when the voltage falls. The inventors have found that the piezoelectric film 15 in which the number of current peaks in the IV curve differs between the rise and fall of the voltage in this manner exhibits higher withstand voltage and reliability than a piezoelectric film in which the number of peaks is the same between the rise and fall of the voltage (see Examples described later). As described above, it is believed that the stress between the substrate 10 and the piezoelectric film 15 is higher than in the past, resulting in high withstand voltage and reliability.
[0046] The piezoelectric stack 5 and the piezoelectric element 1 may include, in addition to the lower electrode layer 12 and the piezoelectric film 15, other layers such as an adhesion layer and a seed layer.
[0047] "Second embodiment" Fig. 3 is a schematic cross-sectional view of a piezoelectric element 2 of the second embodiment. The same components as those of the piezoelectric element 1 of the first embodiment shown in Fig. 1 are denoted by the same reference numerals. The piezoelectric element 2 includes a substrate 10 and a piezoelectric stack 5A. The piezoelectric stack 5A differs from the piezoelectric stack 5 in that a seed layer 13 is provided between the lower electrode layer 12 and the piezoelectric film 15.
[0048] The seed layer 13 is lattice-matched with the perovskite oxide that is the main component of the piezoelectric film 15. By providing the seed layer 13, it is possible to improve the crystallinity of the piezoelectric film 15 formed thereon. The piezoelectric film 15 formed on the seed layer 13 may be an epitaxial film that is epitaxially grown.
[0049] The seed layer 13 preferably has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudocubic crystal. When the lattice constant is in this range, it is lattice-matched with perovskite oxide, particularly Nb-doped PZT, and therefore when the piezoelectric film 15 formed on the upper layer is Nb-doped PZT, its crystallinity can be improved. The lattice constant of each layer can be measured by XRD (X-Ray Diffraction) analysis.
[0050] The seed layer 13 is preferably conductive. Here, being conductive means that the seed layer 13 has an electrical resistivity of such a degree that it can function as an electrode. Here, the electrical resistivity at 20° C. is 10 -5 A seed layer 13 having a conductivity of Ω·m or less can function as an electrode for applying a driving voltage to the piezoelectric film 15 together with the lower electrode layer 12 if the seed layer 13 is conductive.
[0051] Examples of the main components of the seed layer 13 include SrRuO3, BaRuO3, and PbTiO3. These have a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudocubic crystal. As the main component of the seed layer 13, SrRuO3 or BaRuO3, which is particularly conductive, is preferable.
[0052] The piezoelectric stack 5A and the piezoelectric element 2 differ from the piezoelectric stack 5 and the piezoelectric element 1 in that they include a seed layer 13 between the lower electrode layer 12 and the piezoelectric film 15, but the other configurations are similar to those of the piezoelectric stack 5 and the piezoelectric element 1, and similar effects can be obtained. Furthermore, by including the seed layer 13, the piezoelectric stack 5A and the piezoelectric element 2 can obtain a further improvement in the piezoelectric constant compared to when the seed layer 13 is not provided.
[0053] The piezoelectric elements 1 and 2 or the piezoelectric laminates 5 and 5A in the above-described embodiments are applicable to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES
[0054] Specific examples and comparative examples of the piezoelectric element of the present disclosure will be described below. First, a method for producing the piezoelectric element of each example will be described. A sputtering device was used to deposit each layer. The description of the production method will be made with reference to the reference numerals of each layer of the piezoelectric element 1 shown in FIG.
[0055] (Production method) As the substrate 10, a silicon substrate with a thermal oxide film was used.
[0056] A substrate with an electrode layer was prepared by sequentially stacking an adhesion layer made of Ti and having a thickness of 20 nm, a lower electrode layer 12 made of Pt and having a thickness of 150 nm, and a seed layer 13 made of SrRuO3 and having a thickness of 20 nm on a thermal oxide film of a substrate 10.
[0057] <Piezoelectric film> On the seed layer 13, a Nb-added PZT film was formed as the piezoelectric film 15 under the following sputtering conditions. A Nb-added PZT target was used for the film formation. The Pb composition ratio was 1.3, and the Zr / Ti molar ratio was an MPB composition (Zr / Ti=52 / 48), that is, a target with x=0.52 and Nb composition ratio y=0.12 was used. In each example, a pretreatment was performed under the conditions shown in Table 1 immediately before the formation of the piezoelectric film 15. For example, in the case of Example 1, the substrate bias voltage was -40V and the input power was 0.5kW. The pretreatment time was 3 minutes. The conditions other than the substrate bias voltage and input power shown in Table 1 were the same as the sputtering conditions for the piezoelectric film. In Comparative Example 1, there was no pretreatment, and in Comparative Example 2, the substrate bias voltage during the pretreatment was the same voltage as during the film formation.
[0058] -Sputtering conditions for piezoelectric film- Target-substrate distance: 100mm Target input power: 3kW Degree of vacuum (film formation pressure): 0.5Pa Atmosphere: Ar / O2 mixture (O2 volume fraction 2.5%) Substrate temperature setting: 550℃ Substrate bias voltage: +40V
[0059] <Top electrode layer> An ITO layer having a thickness of 100 nm was formed as an upper electrode layer 18 on the piezoelectric film 15 of the above-mentioned laminated substrate by sputtering.
[0060] <Formation of electrode pattern for evaluation> Before forming the upper electrode layer 18, a resist pattern was formed by photolithography, the upper electrode layer 18 was formed on the resist pattern, and an upper electrode pattern for evaluation was formed by lift-off.
[0061] Through the above steps, laminates of the comparative example and the example were produced.
[0062] [Table 1]
[0063] (Preparation of evaluation samples) -Evaluation sample 1- A rectangular piece measuring 2 mm×25 mm was cut out from the laminate to prepare a cantilever as evaluation sample 1.
[0064] -Evaluation sample 2- A 25 mm×25 mm portion having upper electrode layer 18 patterned in a circle with a diameter of 400 μm at the center of the surface of piezoelectric film 15 was cut out from the laminate to provide evaluation sample 2.
[0065] <Measurement of current-voltage characteristics> The IV curves were measured for the piezoelectric elements of each Example and Comparative Example using the evaluation sample 2. The measurement was performed using a ferroelectric property evaluation system FEC10 manufactured by Toyo Corporation. For the piezoelectric elements of each Example and Comparative Example, the lower electrode layer 12 was grounded, and the potential applied to the upper electrode layer 18 was changed from 0V to +40V to -40V to 0V under the condition of a frequency of 10Hz, and the IV curves were obtained at that time. The measurement of the IV curve was performed with a change of 0V to +40V to -40V to 0V as one cycle, and the coercive field value was determined from the data of the third cycle. As already mentioned, in the measurement of the IV curve, the first cycle is unstable, and from the second cycle onwards, the IV curve is stable and approximately the same IV curve is obtained. Here, the data of the third cycle was used to be sure. Parts of the obtained IV curves are shown in Figs. 4 and 5. Fig. 4 shows the IV curve of Example 3, and Fig. 5 shows the IV curve of Comparative Example 1.
[0066] As shown in Fig. 4, the IV curve of Example 3 has three peaks when the voltage rises and two peaks when the voltage falls. In contrast, as shown in Fig. 5, the IV curve of Comparative Example 1 has only one peak each when the voltage rises and falls. The number of peaks NA when the voltage rises and the number of peaks NB when the voltage falls for each Example and Comparative Example are as shown in Table 2.
[0067] <Measurement of piezoelectric constant> Using a cantilever, the piezoelectric constant d was measured by applying a sine wave voltage of -10 V±10 V, i.e., a bias voltage of -10 V plus a sine wave with an amplitude of 10 V, according to the method described in I. Kanno et. al. Sensor and Actuator A 107 (2003) 68. 31 The results are shown in Table 2.
[0068] The piezoelectric constant was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A: 200pm / V or more B: 170pm / V or more, less than 200pm / V C: Less than 170pm / V
[0069] <Evaluation of withstand voltage> The withstand voltage (dielectric breakdown voltage) of each example and comparative example was measured. Using evaluation sample 2, lower electrode layer 12 was grounded, and a negative voltage was applied to upper electrode layer 18 at a rate of change of -1V / sec. The voltage at which a current of 1 mA or more flowed was regarded as the withstand voltage. Ten samples were prepared for each example, and measurements were performed ten times in total. The average value (absolute value) is shown in Table 2 as the withstand voltage [V].
[0070] The withstand voltage was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A:100V or more B: 60V or more, less than 100V C: Less than 60V
[0071] <Evaluation of driving stability (reliability)> A time dependent dielectric breakdown (TDDB) test was conducted to evaluate the driving stability of each of the examples and comparative examples. Using evaluation sample 2, the lower electrode layer 12 was grounded in an environment of 120° C., and a voltage of −40 V was applied to the upper electrode layer 18, and the time (hr) from the start of voltage application until dielectric breakdown occurred was measured. The measurement results are shown in Table 2. The TDDB test was conducted for 2000 hours, and those that did not experience dielectric breakdown up to 2000 hours are listed as 2000 in Table 2.
[0072] Reliability was evaluated according to the following criteria, and the evaluation results are shown in Table 2. A:1000hr or more B: 700 hours or more, less than 1000 hours C: Less than 700 hours
[0073] <Method of measuring crystal grain size> The surface of the piezoelectric film after deposition, i.e., the surface of the piezoelectric film before the upper electrode was deposited, was measured by EBSD. The measuring devices used were a JEOL JSM-7001F SEM (Scanning Electron Microscope) and an EBSD OIM manufactured by TSL. Figure 6 shows the image pattern of crystal grains on the surface of the piezoelectric film obtained by the EBSD method. The crystal grains were identified in the image pattern shown in Figure 6, and the smallest circumscribed circle was determined for each grain, and the diameter of the circumscribed circle was determined as the crystal grain size. The average grain size was then calculated as a weighted average based on the area ratio of the crystal grain size. The average grain size for each example and comparative example was as shown in Table 2.
[0074] In addition, in Table 2, the lowest evaluation result among the evaluations of the piezoelectric constant, the withstand voltage, and the reliability for each of the examples and comparative examples is shown as an overall evaluation. [Table 2]
[0075] The piezoelectric constant was comparable in Comparative Examples 1 and 2 and Examples 1 to 5, but in Examples 1 to 5, in which a pretreatment was performed in which the substrate bias voltage was reversed in polarity from that during film formation before the piezoelectric film was formed, the withstand voltage and reliability were significantly improved compared to Comparative Examples 1 and 2. In the element that obtained such high withstand voltage and reliability, the number of peaks NA when the voltage of the IV curve increased was 1 greater than the number of peaks NB when the voltage decreased, and the half-width Wu of the peaks when the voltage increased was 1.2 times or more greater than the half-width Wd of the peaks when the voltage decreased. When the peak half-width ratio Wu / Wd was 1.5 or more, higher withstand voltage and reliability were obtained.
[0076] All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference.
[0077] The following supplementary notes are further disclosed regarding the above embodiment. <Appendix 1> A piezoelectric laminate including a lower electrode layer and a piezoelectric film mainly composed of a perovskite oxide, in this order, on a substrate, A piezoelectric laminate in which an upper electrode layer is formed on the piezoelectric film, and the voltage applied between the upper electrode layer and the lower electrode layer is swept, the lower electrode layer is grounded, the upper electrode layer is used as a driving electrode, and the voltage applied to the piezoelectric film is gradually increased from 0 V to the positive side, and then decreased to the negative side via 0 V, in a current-voltage curve showing the change in current relative to the change in voltage, the number of peaks when the voltage is increasing is different from the number of peaks when the voltage is decreasing. <Appendix 2> The piezoelectric laminate described in Appendix 1, wherein, when the peak half-width when the voltage increases in the current-voltage curve is Wu and the peak half-width when the voltage decreases is Wd, Wu≧1.5×Wd. <Appendix 3> 3. The piezoelectric stack according to claim 1 or 2, wherein NA>NB, where NA is the number of peaks during the increase in voltage and NB is the number of peaks during the decrease in voltage. <Appendix 4> 4. The piezoelectric stack of claim 3, wherein the number of peaks NA during the voltage increase is one greater than the number of peaks NB during the voltage decrease. <Appendix 5> 4. The piezoelectric stack according to claim 3, wherein the number of peaks NA during the voltage increase is 3, and the number of peaks NB during the voltage decrease is 2. <Appendix 6> The perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y M y}O3 M is a metal element selected from the group consisting of V, Nb, Ta, Sb, Mo and W; 0 <x<1、0<y<1、0.9≦a≦1.2 6. The piezoelectric laminate according to claim 1, wherein <Appendix 7> 7. The piezoelectric laminate according to claim 6, wherein M is Nb and satisfies 0.08≦y≦0.15. <Appendix 8> The piezoelectric laminate according to any one of claims 1 to 7, wherein the piezoelectric film has an average grain size of 0.3 μm or more, weighted by the area ratio of the crystal grain size, in a crystal grain size distribution obtained by electron backscatter diffraction. <Appendix 9> 9. The piezoelectric stack of claim 1, further comprising a seed layer between the lower electrode layer and the piezoelectric film, the seed layer being lattice-matched to the perovskite oxide. <Appendix 10> 10. The piezoelectric stack according to claim 9, wherein the seed layer has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal. <Appendix 11> 11. The piezoelectric stack according to claim 9 or 10, wherein the seed layer is mainly composed of SrRuO3 or BaRuO3. <Appendix 12> A piezoelectric laminate according to any one of claims 1 to 11; an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. [Explanation of symbols]
[0078] 1, 2 Piezoelectric element 5, 5A Piezoelectric laminate 10 Substrate 12 Lower electrode layer 13 Seed layer 15 Piezoelectric film 18 Upper electrode layer
Claims
1. A piezoelectric laminate including a lower electrode layer and a piezoelectric film mainly composed of a perovskite oxide, in this order, on a substrate, A piezoelectric laminate in which, when an upper electrode layer is formed on the piezoelectric film, and a voltage applied between the upper electrode layer and the lower electrode layer is swept, the lower electrode layer is grounded, and the upper electrode layer is used as a driving electrode, and the voltage applied to the piezoelectric film is gradually increased from 0 V to a positive side, and then gradually decreased from the positive side to 0 V to a negative side, in a current-voltage curve showing a change in current with respect to the change in voltage, the number of peaks when the voltage is increasing is different from the number of peaks when the voltage is decreasing.
2. 2. The piezoelectric stack according to claim 1, wherein, when a half-width of a peak when the voltage rises in the current-voltage curve is Wu and a half-width of a peak when the voltage falls is Wd, Wu≧1.5×Wd.
3. 3. The piezoelectric laminate according to claim 1, wherein NA is the number of peaks during the rise of the voltage, and NB is the number of peaks during the fall of the voltage, and NA>NB.
4. 4. The piezoelectric stack according to claim 3, wherein the number of peaks NA during the voltage rise is greater by 1 than the number of peaks NB during the voltage fall.
5. 4. The piezoelectric stack according to claim 3, wherein the number of peaks NA during the voltage rise is 3, and the number of peaks NB during the voltage fall is 2.
6. The perovskite oxide is Pb a {(Zr x Ti 1-x ) 1-y M y }O 3 M is a metal element selected from the group consisting of V, Nb, Ta, Sb, Mo and W; 0<x<1, 0<y<1, 0.9≦a≦1.2 The piezoelectric laminate according to claim 1 or 2, which satisfies the above.
7. The piezoelectric stack according to claim 6 , wherein M is Nb and satisfies 0.08≦y≦0.
15.
8. 3. The piezoelectric laminate according to claim 1, wherein the piezoelectric film has an average grain size of 0.3 μm or more, weighted by an area ratio of the crystal grain size, in a crystal grain size distribution obtained by electron backscatter diffraction.
9. 3. The piezoelectric stack according to claim 1, further comprising a seed layer between the lower electrode layer and the piezoelectric film, the seed layer being lattice-matched with the perovskite oxide.
10. 10. The piezoelectric stack according to claim 9, wherein the seed layer has a lattice constant of 0.39 nm to 0.405 nm when considered as a pseudo cubic crystal.
11. The seed layer is made of SrRuO 3 or BaRuO 3 The piezoelectric laminate according to claim 9, which is mainly composed of
12. The piezoelectric laminate according to claim 1 or 2; an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.
Citation Information
Patent Citations
Piezoelectric device and liquid discharge apparatus using the same
JP2009071295A
Piezoelectric device and using method thereof
JP2014060330A
Composition for forming manganese- and niobium-doped PZT piezoelectric film
WO2015146607A1